2012
DOI: 10.1097/gme.0b013e318252e450
|View full text |Cite
|
Sign up to set email alerts
|

Receptors for thyrotropin-releasing hormone, thyroid-stimulating hormone, and thyroid hormones in the macaque uterus

Abstract: All receptors involved in thyroid hormone function are expressed in monkey uterus, and they are all regulated by long-term steroid hormone treatment. These findings suggest that there is a possibility of direct actions of thyroid hormones, thyroid-stimulating hormone and thyrotropin-releasing hormone on uterine function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 32 publications
1
14
0
2
Order By: Relevance
“…The roles of thyroid hormones in uterine physiology and function have received more attentions since the identification of functional thyroid receptors in uteri [ 5 , 13 , 14 ]. From the results of immunohistochemistry, we confirmed that TRα/β was present and located in different cell types of rat uteri, which suggested that there was an important relationship between thyroid hormones and uterine development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The roles of thyroid hormones in uterine physiology and function have received more attentions since the identification of functional thyroid receptors in uteri [ 5 , 13 , 14 ]. From the results of immunohistochemistry, we confirmed that TRα/β was present and located in different cell types of rat uteri, which suggested that there was an important relationship between thyroid hormones and uterine development.…”
Section: Discussionmentioning
confidence: 99%
“…Results from previous investigations, strongly suggest the existence and expression of these receptors in different tissues [ 12 ]. Moreover, several studies have demonstrated that thyroid hormone receptors are expressed in female reproductive organs, such as the human endometrium [ 5 ], macaque uterus [ 13 ] and rat ovary [ 8 ], uterus and oviduct [ 14 ].…”
mentioning
confidence: 99%
“…Thyroid hormones can influence reproductive function through their effects on gonadotropin-releasing hormone pulse generation, prolactin release, sex hormone-binding globulin turnover, and by binding to thyroid hormone receptors (THRs) in the reproductive tract. 7 The human ovary 43 and the uterus of cynomolgus macaques 44 express THRs. It is possible that THRs are also present in the macaque ovary and function as they do in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Diseases causing overt hyperthyroidism or hypothyroidism can also induce menstrual disorders and fertility consequences. In animal studies, all receptors in the signaling pathway of thyroid hormone function including thyrotropin-releasing hormone (TRH), thyroid-stimulating hormone (TSH), and thyroid hormones were shown to be present in monkey uterus and influenced by long-term steroid hormone treatment (10).…”
Section: Introductionmentioning
confidence: 99%